Quantifying the road‐effect zone for a critically endangered primate. Issue 6 (15th September 2021) - Andrasi, Balint; Jaeger, Jochen A.G.; Heinicke, Stefanie; Metcalfe, Kristian; Hockings, Kimberley J.
Abstract: The global road network is expanding at an unprecedented rate, threatening the persistence of many species. Yet, even for the most endangered wildlife, crucial information on the distance up to which roads impact species abundance is lacking. Here we use ecological threshold analysis to quantify the road‐effect zone (REZ) for the critically endangered western chimpanzee ( Pan troglodytes verus ). We found: (1) the REZ extends 5.4 km (95% CI [4.9–5.8 km]) from minor roads and 17.2 km (95% CI [15.8–18.6]) from major roads, the latter being more than three times wider than a previous estimate of the average REZ for mammals; and (2) only 4.3% of the chimpanzees' range is not impacted by existing roads. These findings reveal the high sensitivity and susceptibility of nonhuman primates to roads across West Africa, a region undergoing rapid development, and can inform the implementation of more effective guidelines to mitigate road impacts.